Whole-series recovery process for waste lithium ion batteries

By combining pretreatment, microwave baking, eddy current separation, and infrared irradiation, the problems of low recycling rate and poor quality of recycled materials from waste lithium-ion batteries have been solved, achieving efficient and environmentally friendly lithium-ion battery recycling and improving recycling rate and purity.

CN121123472APending Publication Date: 2025-12-12INST OF ENERGY HEFEI COMPREHENSIVE NAT SCI CENT (ANHUI ENERGY LAB)

Patent Information

Application Number
CN202511362088.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-23
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing waste lithium-ion battery recycling technologies suffer from low recycling rates, poor quality of recycled materials, high levels of impurities, and environmental unfriendliness. In particular, the separation of positive and negative electrode powders leads to mutual mixing of the powders and low recycling efficiency.

Method used

The process employs a combination of pretreatment, microwave baking, eddy current separation, spectral color sorting, and infrared irradiation. This includes microwave baking in a vacuum environment to recover the electrolyte, using eddy current separation to separate the negative electrode, using spectral color sorting to separate the positive electrode and the separator, and using infrared irradiation to separate the positive and negative electrode powders and the current collector.

Benefits of technology

It improves the recycling rate of waste lithium-ion batteries and the purity of recycled materials, simplifies the process, reduces environmental pollution, improves work efficiency, and reduces the content of metal impurities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121123472A_ABST
    Figure CN121123472A_ABST
Patent Text Reader

Abstract

The invention discloses an all-series recovery process for waste lithium ion batteries, which belongs to the field of lithium battery regeneration and comprises the main process steps of pretreatment of the waste lithium ion batteries, electrolyte recovery through microwave baking, obtaining of positive plates and negative plates through eddy current separation and separation of positive and negative black powder and metal foil through infrared irradiation. Wherein the electrolyte is recovered through microwave baking, so that the electrolyte can be quickly vaporized and then condensed and recovered under the action of microwaves by utilizing the strong polarity of the electrolyte, and therefore, the electrolyte can be efficiently separated, the removal effect is more thorough, and the problem of electrolyte pollution cannot be generated in the process. According to the infrared irradiation separation process, the absorption capacity of different adhesives to different infrared wavelengths can be utilized, and the molecular chains of the adhesives are broken and the positive and negative electrode powder and the metal foil can be automatically stripped by adjusting the irradiation infrared band and generating resonance vibration, so that the residues of the adhesives are greatly reduced; the recovery rate of the waste lithium ion battery and the purity of the recovered material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery recycling, and in particular to a process for the complete recycling of waste lithium-ion batteries. Background Technology

[0002] Lithium-ion batteries are a widely used energy storage technology with advantages such as high energy density and long cycle life. They are characterized by the reversible insertion / extraction of lithium ions between electrodes and are now widely used in many fields such as consumer electronics, power tools and defense equipment, and have become one of the core components of new energy vehicles.

[0003] With the rapid development of the new energy industry and the expansion of energy storage demand, the consumption of lithium-ion batteries has surged, and the amount of waste lithium-ion batteries generated has also increased accordingly. The heavy metals, organic solvents, and electrolytes contained in waste lithium-ion batteries can pollute the environment, threatening ecosystems and human health. Furthermore, waste lithium-ion batteries are rich in recyclable components such as copper, aluminum, and graphite; failure to effectively recycle them would result in a huge waste of resources. Therefore, the recycling of waste lithium-ion batteries has become a focus of attention.

[0004] Waste lithium-ion batteries mainly consist of positive electrode current collectors (usually aluminum foil), negative electrode current collectors (usually copper foil), battery separators, electrolytes, binders, and black powder. The key to recycling waste lithium-ion batteries lies in effectively separating these components, specifically recovering the copper foil, aluminum foil, and black powder. However, existing physical sorting methods have many problems, resulting in low recycling rates and poor quality of recycled products. Particularly during the separation of positive and negative electrode powders, there is the issue of cross-mixing between the powders and low recycling efficiency.

[0005] To address these issues, a method has been used to first separate the positive and negative electrode powders through physical sorting, and then extract valuable metal elements using hydrometallurgy to recycle spent lithium-ion batteries. However, this method is inefficient, with low recovery rates of the positive and negative electrode powders, and contains large amounts of aluminum and copper metal impurities, increasing the difficulty of separation in the subsequent hydrometallurgical process. Furthermore, the recycling process involves large amounts of acids and alkalis, making the process complex. Moreover, direct wet separation during recycling can lead to the leakage of toxic electrolytes, causing environmental pollution.

[0006] Alternatively, a recycling method for waste lithium-ion batteries is proposed in Chinese patent application CN117655066A. This method involves discharging the waste lithium-ion batteries, crushing and separating the positive and negative electrode sheets, then heating and drying them before sorting them using a magnetic separator. While this method effectively prevents electrolyte leakage, electrolyte remains in the crushed material, failing to fundamentally solve the problem of electrolyte contamination. Furthermore, this method primarily uses a hammer crusher to separate the positive and negative electrode powder and current collectors. The binder structure in the positive electrode sheet remains intact, resulting in high bonding strength, making the separation of electrode powder difficult during crushing. Moreover, prolonged impact separation may damage the surfaces of the positive and negative current collectors, allowing metallic impurities such as copper and aluminum foil to enter the electrode powder, increasing the cost of impurity treatment in subsequent hydrometallurgical processes.

[0007] Currently, the recycling and regeneration methods for waste lithium-ion batteries still face many problems and challenges. Therefore, there is an urgent need for a more efficient, safe, and environmentally friendly recycling process for waste lithium-ion batteries that can significantly improve the recycling rate of lithium-ion batteries, reduce metal impurities in the recycled materials, and reduce environmental pollution during the process. Summary of the Invention

[0008] This invention provides a complete recycling process for waste lithium-ion batteries, which can solve the problems of low recycling rate, poor quality of recycled materials, high impurity content, and environmental unfriendliness in the recycling process of waste lithium-ion batteries in the existing technology.

[0009] A process for the complete recycling of spent lithium-ion batteries includes the following steps: S1. Waste lithium-ion batteries are pretreated to obtain regular sheet-like materials; S2. The sheet-like regular material is microwave-baked in a vacuum environment, and the electrolyte is condensed and recovered along with the solid material. S3. The recovered solid material is evenly spread into layers, and the negative electrode is separated by eddy current separation; then the positive electrode and the separator are separated by spectral color sorting. S4. The positive and negative electrode sheets are irradiated under infrared light, and then separated by sieve to recover aluminum foil and copper foil respectively.

[0010] Preferably, the diameter of the regular sheet material is 1 to 4 cm.

[0011] Preferably, the waste lithium-ion batteries include ternary lithium batteries and lithium iron phosphate batteries.

[0012] More preferably, the thickness of the material uniformly laid in step S3 is ≤2mm.

[0013] More preferably, in step S3, the eddy current magnetic field strength during the eddy current separation process is 300–400 Hz.

[0014] More preferably, in step S3, the resolution of spectral color sorting is 0.1 mm and the scanning speed is 10 m / s.

[0015] By adopting the above technical solution, the recycled waste lithium-ion batteries are first pre-treated and crushed into regular sheet-like materials, which is beneficial for subsequent recycling operations. The obtained regular sheet-like materials are then microwave-baked. The electrolyte solvent in the materials consists of highly polar molecules with a strong ability to absorb microwaves. Therefore, it will rapidly vaporize due to the absorption of microwave energy, forming mixed vapors. The regular sheet-like structure increases the specific surface area of ​​the material, which helps microwaves and pyrolysis heat to penetrate more evenly, making it easier for pyrolysis gases to escape.

[0016] Furthermore, because microwave baking is carried out in a vacuum environment, the vapor generated by the vaporization of the electrolyte is immediately and quickly extracted by negative pressure, and then condensed back into liquid droplets, thereby achieving effective recovery of the electrolyte. Moreover, the electrolyte will not overflow during the recovery process, thus preventing environmental pollution.

[0017] The solid material, after the electrolyte solvent has been removed, is then subjected to eddy current separation. Since the negative electrode contains copper foil as a negative current collector, when it enters the alternating magnetic field region formed by the staggered and rotating poles of the permanent magnet, eddy currents are generated within it due to the difference in conductivity between the materials. These eddy currents create opposing magnetic fields within the material, generating a repulsive force, thus effectively separating the negative electrode from other materials. Maintaining the regular, sheet-like structure efficiently generates eddy currents, preserving the conductivity continuity of the copper foil in the negative electrode. Compared to irregular particles, the regular, sheet-like structure exhibits a higher eddy current separation recovery rate.

[0018] Then, based on the color difference between the positive electrode and the separator surface, the positive electrode and the separator are effectively separated by spectral color sorting.

[0019] Finally, infrared processing can effectively separate the positive and negative electrode powders and the positive and negative electrode current collectors, namely aluminum foil and copper foil. Traditional separation methods often use mechanical crushing, but this method is difficult to control the material morphology precisely. Over-crushing can also cause aluminum foil and copper foil to form micron-sized mixed particles with the positive and negative electrode powders. The particle size is too small to be separated by magnetic separation, resulting in low purity of the recovered product and poor recovery efficiency. On the other hand, the binders contained in the positive and negative electrode sheets are difficult to remove. Low-temperature pyrolysis also has the problem of incomplete decomposition, causing the positive and negative electrode powders and current collectors to stick together. The residual binders will greatly affect the purity of the recovered aluminum foil, copper foils, and positive and negative electrode powders, resulting in the loss of the value of the recovered metals.

[0020] The present invention uses infrared irradiation to process the material, which can effectively break the molecular chains of the adhesive, achieve rapid and effective separation between the current collector and the electrode, and preserve the structure of the material, enabling the complete recycling of aluminum foil and copper foil with high recovery rate and high purity of the recycled product.

[0021] Preferably, step S4 specifically includes: S401. Irradiate the positive electrode sheet in the mid-infrared band for 10-30 seconds, and then sieve it through a drum screen to separate the positive electrode black powder and aluminum foil; S402. Irradiate the negative electrode sheet in the short infrared band for 20-40 seconds, and then sieve it through a drum screen to separate the negative electrode black powder and copper foil.

[0022] Preferably, the mid-infrared band includes 5.5–6.5 μm; the short-infrared band includes 2.5–3.5 μm.

[0023] Preferably, the power density of the irradiation in step S401 is 8–12 kW / m². 2 The power density of irradiation in step S402 is 5–8 kW / m³. 2 .

[0024] More preferably, the diameter of the drum screen mesh is 100 mesh, and the rotation speed is 10-15 rpm.

[0025] By adopting the above technical solution, this invention utilizes the different types of binders used in the positive and negative electrode sheets and selects different bands of infrared radiation for irradiation treatment. Specifically, polyvinylidene fluoride binder is usually used in the positive electrode sheet of lithium-ion batteries. This type of binder has a strong absorption rate in the mid-infrared band. Under infrared irradiation in this band, it can resonate and vibrate with the molecular chains of the binder, causing the molecular chains to break and gradually decompose, resulting in a sharp drop in the interfacial bonding force between the positive electrode powder and the current collector aluminum foil. The two can automatically peel off and then be screened through a drum screen to separate the positive electrode black powder and aluminum foil.

[0026] For lithium-ion battery negative electrode sheets, sodium carboxymethyl cellulose is usually used as a binder. This type of binder has a strong absorption rate in the short infrared band and can achieve fracture carbonization under short infrared irradiation, thereby effectively separating the negative electrode black powder and the current collector copper foil.

[0027] Compared to traditional mechanical friction shearing stripping, the infrared irradiation method described above can effectively avoid deformation or low purity issues in recycled aluminum and copper foils. Moreover, this method has low energy consumption, releases no harmful gases, requires no chemical reagents, and is highly efficient. It can complete the decomposition of the binder and the separation between the electrode powder and the metal foil in a very short time, which can greatly improve the recovery rate and purity of positive and negative electrode powder and metal foil from waste lithium-ion batteries and simplify the process.

[0028] Preferably, the preprocessing in step S1 specifically includes: S101. Immerse the waste lithium-ion batteries in the pretreatment solution and discharge them until the voltage of the waste lithium-ion batteries is <0.05V. S102. Under an inert gas atmosphere, the discharged waste lithium-ion batteries are disassembled and crushed to obtain regular sheet-like materials.

[0029] Preferably, the pretreatment solution comprises the following raw materials in the following mass fractions: 4.5-5.5% sodium chloride, 0.05-0.2% alkyl sulfate, and the balance water; the alkyl sulfate includes one or more combinations of sodium dodecyl sulfate, ammonium dodecyl sulfate, sodium dodecyl ether sulfate, sodium octyl sulfate, and sodium hexadecyl sulfate.

[0030] Preferably, the solid-liquid ratio of the waste lithium-ion battery and the pretreatment solution is 1g:(4-6)mL.

[0031] More preferably, the inert gas atmosphere includes an argon atmosphere and a nitrogen atmosphere.

[0032] By adopting the above technical solution, the waste lithium-ion batteries are pre-treated. Specifically, the waste lithium-ion batteries are first discharged, which can prevent thermal runaway explosions caused by short circuits during disassembly or crushing of charged batteries, thus ensuring the safety of subsequent processes. The waste lithium-ion batteries are immersed in a pretreatment solution. The free ions generated by the ionization of sodium chloride in water can penetrate to the positive and negative electrodes of the battery, forming an external ionic conductive path, enabling rapid battery discharge. Furthermore, alkyl sulfates are added to the pretreatment solution.

[0033] During discharge, especially when the initial voltage of recycled lithium-ion batteries is high, the aqueous solution can generate a large amount of hydrogen gas due to side reactions at the negative electrode. Excessive hydrogen concentration poses an explosion risk. The addition of alkyl sulfates can encapsulate the generated hydrogen gas, forming abundant foam in the pretreatment solution. This foam significantly increases the surface area of ​​the gas, allowing it to quickly release from the liquid surface and diffuse into the atmosphere, avoiding the problem of excessively high local hydrogen concentrations and improving the safety of the process.

[0034] Moreover, the introduction of alkyl sulfates can significantly reduce the surface tension of the pretreatment solution, making it easier for the pretreatment solution to penetrate into the tiny gaps in the battery, ensuring a full connection between the battery interior and the discharge circuit, thereby improving recycling efficiency and shortening process time.

[0035] Preferably, the microwave baking temperature is 90–110°C and the baking time is 10–30 minutes.

[0036] More preferably, the vacuum degree in the vacuum environment during microwave baking is 0.7 to 0.8 kPa.

[0037] By adopting the above technical solution, after pre-treating the waste lithium-ion batteries, the present invention first performs microwave baking treatment. Common electrolyte solvents such as ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are all strongly polar molecules. When microwaves penetrate the material, the polar molecules inside the material have a strong absorption capacity for microwaves and will continuously adjust their orientation with the direction of the high-frequency alternating electromagnetic field, thereby generating violent friction and collisions, instantly converting microwave energy into heat energy. The electrolyte will then be rapidly heated and vaporized. The electrode materials, including positive electrode powder, negative electrode powder, and current collectors, are all non-polar or weakly polar substances with a very weak absorption capacity for microwaves. Therefore, the electrolyte in the sheet-like regular material can be selectively and effectively removed, and the problems of overheating, oxidation, or damage that may exist in the electrode matrix material can also be avoided. This is beneficial to maintaining the physical morphology of the sheet-like regular material and provides possibilities for subsequent regeneration and recycling steps.

[0038] After the electrolyte vaporizes, the negative pressure generated by the vacuum pump will quickly remove the vaporized electrolyte because the microwave baking is carried out in a vacuum environment. Then, the electrolyte will re-condense into liquid droplets in the condensation device, thereby achieving full recovery of the electrolyte.

[0039] This recycling method effectively preserves the structure of the flaky, regular material while selectively removing only the electrolyte components. Furthermore, due to internal microwave heating, it efficiently separates the electrolyte hidden deep within the pores of the electrode material, resulting in more thorough material removal without causing electrolyte contamination.

[0040] The beneficial effects of this invention are: 1. In the complete recycling process of waste lithium-ion batteries provided by the present invention, the waste lithium-ion batteries are first pretreated by immersing them in a pretreatment solution to fully discharge them, which can ensure the safety of the process and improve the efficiency of the process. Then, after disassembly and crushing, the waste lithium-ion batteries are obtained as sheet-like regular materials. The sheet-like regular structure can help to penetrate microwaves and pyrolysis heat more evenly in the subsequent microwave baking process, and can also help to maintain the conductivity continuity of copper foil in the negative electrode sheet in the eddy current separation process, thereby improving the recovery rate of eddy current separation.

[0041] 2. In the whole-system recycling process of waste lithium-ion batteries, the present invention uses microwave baking to recover electrolyte. It can utilize the strong polarity of the electrolyte to quickly vaporize under the action of microwaves, and then condense into droplets for recovery. This can efficiently separate the electrolyte, remove it more thoroughly, and the process is simple and will not cause electrolyte pollution.

[0042] 3. This invention utilizes infrared irradiation in the complete recycling process of waste lithium-ion batteries to effectively separate the positive and negative electrode powders and current collectors in the positive and negative electrode sheets. By leveraging the absorption capabilities of different infrared wavelengths of the different binders used in the positive and negative electrode sheets, the infrared irradiation band is adjusted to achieve the decomposition of the binder. The positive and negative electrode powders and metal foils can be automatically peeled off, greatly reducing the residue of the binder. Compared with the shear force peeling of traditional mechanical friction, this method can solve the problems of deformation or low purity of recycled aluminum and copper foils. Moreover, this method is highly efficient, completing the decomposition of the binder and the separation between the electrode powders and metal foils in a very short time. This can greatly improve the recovery rate and purity of the positive and negative electrode powders and metal foils from waste lithium-ion batteries, and simplify the process flow. Attached Figure Description

[0043] Figure 1 This is a process flow diagram of Embodiment 1 of the present invention. Detailed Implementation

[0044] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.

[0045] Example

[0046] Example 1: A process for the complete recycling of waste lithium-ion batteries, comprising the following steps: S1. Waste lithium-ion batteries are pretreated to obtain regularly shaped, sheet-like materials, specifically: S101. The waste lithium-ion battery, i.e. the waste ternary lithium battery, is immersed in a pretreatment solution for discharge. The solid-liquid ratio of the waste ternary lithium battery to the pretreatment solution is 1g:5mL. The pretreatment solution includes 5% sodium chloride, 0.1% sodium dodecyl sulfate and the remainder water by mass. During the discharge process, an external high-precision voltmeter is used to monitor the voltage of the waste ternary lithium battery until the voltage of the waste lithium-ion battery is <0.05V. S102. Under a nitrogen atmosphere, the discharged waste ternary lithium batteries are disassembled and crushed to obtain regular sheet-like materials, wherein the sheet-like materials have a diameter of 1 to 4 cm. S2. The obtained sheet-like regular material is microwave-baked in a vacuum environment, wherein the vacuum degree is controlled at 0.8 kPa, the baking temperature is 100℃, and the baking time is 20 min. Then the electrolyte is condensed and recovered and the solid material is recovered. S3. The recycled solid material is fed into a vibrating single-layer feeder for uniform layering. The material is spread to a thickness of 2mm and then fed into an eddy current separator via a conveyor belt. The negative electrode sheet is separated by eddy current separation. The eddy current magnetic field strength is 380Hz and the conveyor belt speed is 0.5m / s. The separated negative electrode sheet is sent to the negative electrode sheet collection bin to obtain the negative electrode sheet. The separated positive electrode and separator are sent to the sorting area, and then separated by spectral color sorting. The resolution of spectral color sorting is 0.1 mm and the scanning speed is 10 m / s. The separated positive electrode is sent to the positive electrode collection bin, while the separator falls into the waste bin. S4. The positive and negative electrode sheets are irradiated separately under infrared light, and then separated by sieving to recover the aluminum foil and copper foil respectively. Specifically: S401. The collected positive electrode sheets are fed into an infrared drum screen via a conveyor belt. The drum screen rotates at 15 rpm and is irradiated for 18 seconds in the mid-infrared band, where the mid-infrared wavelength is 5.8 μm and the irradiation power density is 8 kW / m². 2 The conveyor belt speed is 0.3m / min, and then the material is screened through a drum screen to separate the positive electrode black powder and aluminum foil. The positive electrode black powder is recycled to the positive electrode black powder bin, and the aluminum foil is the material left on the screen and is conveyed to the aluminum foil recycling bin by the conveyor belt. S402. The collected negative electrode sheets are fed into an infrared drum screen via a conveyor belt. The drum screen rotates at 15 rpm and is irradiated for 40 seconds in the short infrared band, where the short infrared wavelength is 2.9 μm and the irradiation power density is 5 kW / m². 2 The conveyor belt speed is 0.2m / min, and then the material is screened through a drum screen to separate the negative electrode black powder and copper foil. The negative electrode black powder is recycled to the negative electrode black powder bin, while the copper foil is the material left on the screen and is conveyed to the copper foil recycling bin by the conveyor belt.

[0047] Example 2: A process for the complete recycling of waste lithium-ion batteries, comprising the following process steps: S1. Waste lithium-ion batteries are pretreated to obtain regularly shaped, sheet-like materials, specifically: S101. The waste lithium-ion battery, i.e. the waste ternary lithium battery, is immersed in a pretreatment solution for discharge. The solid-liquid ratio of the waste ternary lithium battery to the pretreatment solution is 1g:5mL. The pretreatment solution includes 5% sodium chloride, 0.1% sodium dodecyl sulfate and the remainder water by mass. During the discharge process, an external high-precision voltmeter is used to monitor the voltage of the waste ternary lithium battery until the voltage of the waste lithium-ion battery is <0.05V. S102. Under a nitrogen atmosphere, the discharged waste ternary lithium batteries are disassembled and crushed to obtain regular sheet-like materials, wherein the sheet-like materials have a diameter of 1 to 4 cm. S2. The obtained sheet-like regular material is microwave-baked in a vacuum environment, wherein the vacuum degree is controlled at 0.8 kPa, the baking temperature is 100℃, and the baking time is 20 min. Then the electrolyte is condensed and recovered and the solid material is recovered. S3. The recycled solid material is fed into a vibrating single-layer feeder for uniform layering. The material is spread to a thickness of 2mm and then fed into an eddy current separator via a conveyor belt. The negative electrode sheet is separated by eddy current separation. The eddy current magnetic field strength is 400Hz and the conveyor belt speed is 0.5m / s. The separated negative electrode sheet is sent to the negative electrode sheet collection bin to obtain the negative electrode sheet. The separated positive electrode and separator are sent to the sorting area, and then separated by spectral color sorting. The resolution of spectral color sorting is 0.1 mm and the scanning speed is 10 m / s. The separated positive electrode is sent to the positive electrode collection bin, while the separator falls into the waste bin. S4. The positive and negative electrode sheets are irradiated separately under infrared light, and then separated by sieving to recover the aluminum foil and copper foil respectively. Specifically: S401. The collected positive electrode sheets are fed into an infrared drum screen via a conveyor belt. The drum screen rotates at 15 rpm and is irradiated for 20 seconds in the mid-infrared band, where the mid-infrared wavelength is 6 μm and the irradiation power density is 10 kW / m². 2 The conveyor belt speed is 0.4m / min, and then the material is screened through a drum screen to separate the positive electrode black powder and aluminum foil. The positive electrode black powder is recycled to the positive electrode black powder bin, and the aluminum foil is the material left on the screen and is conveyed to the aluminum foil recycling bin by the conveyor belt. S402. The collected negative electrode sheets are fed into an infrared drum screen via a conveyor belt. The drum screen rotates at 15 rpm and is irradiated for 30 seconds in the short infrared band, where the short infrared wavelength is 3 μm and the irradiation power density is 6 kW / m². 2 The conveyor belt speed is 0.3m / min, and then the material is screened through a drum screen to separate the negative electrode black powder and copper foil. The negative electrode black powder is recycled to the negative electrode black powder bin, while the copper foil is the material left on the screen and is conveyed to the copper foil recycling bin by the conveyor belt.

[0048] Comparative Example

[0049] Comparative Example 1: A complete recycling process for waste lithium-ion batteries, comprising the following steps: S1. Waste lithium-ion batteries are pretreated to obtain regularly shaped, sheet-like materials, specifically: S101. The waste lithium-ion battery, i.e. the waste ternary lithium battery, is placed in a pretreatment solution for immersion and discharge, wherein the solid-liquid ratio of the waste ternary lithium battery to the pretreatment solution is 1g:5mL, and the pretreatment solution includes 5% sodium chloride, 0.1% sodium dodecyl sulfate and the remainder water by mass fraction. During the discharge process, an external high-precision voltmeter is used to monitor the voltage of the waste ternary lithium battery until the voltage of the waste lithium-ion battery is <0.05V. S102. Under a nitrogen atmosphere, the discharged waste ternary lithium batteries are disassembled and crushed to obtain regular sheet-like materials, wherein the sheet-like materials have a diameter of 1 to 4 cm. S2. The obtained sheet-like regular material is microwave-baked in a vacuum environment, wherein the vacuum degree is controlled at 0.8 kPa, the baking temperature is 100℃, and the baking time is 20 min. Then the electrolyte is condensed and recovered and the solid material is recovered. S3. The recycled solid material is fed into a vibrating single-layer feeder for uniform layering. The material is spread to a thickness of 2mm and then fed into an eddy current separator via a conveyor belt. The negative electrode sheet is separated by eddy current separation. The eddy current magnetic field strength is 380Hz and the conveyor belt speed is 0.5m / s. The separated negative electrode sheet is sent to the negative electrode sheet collection bin to obtain the negative electrode sheet. The separated positive electrode and separator are sent to the sorting area, and then separated by spectral color sorting. The resolution of spectral color sorting is 0.1 mm and the scanning speed is 10 m / s. The separated positive electrode is sent to the positive electrode collection bin, while the separator falls into the waste bin. S4. Mix a 0.5% dilute hydrochloric acid solution with the positive electrode sheet, wherein the liquid-to-solid ratio is 10mL:1g. Add the mixture to a fine crusher, stir and crush for 2 minutes, control the stirring and crushing temperature at 25℃, then filter and separate, and dry to obtain positive electrode black powder and aluminum foil particles. S5. Add the negative electrode sheet to the water, with a liquid-to-solid ratio of 10 mL: 1 g. Add the mixture to a fine crusher, stir and crush for 2 min, control the stirring and crushing temperature at 25 °C, then filter and separate, and dry to obtain negative electrode black powder and copper foil particles.

[0050] Performance testing

[0051] The recovery rates of the positive electrode powder, negative electrode powder, aluminum foil, and copper foil recovered in the examples and comparative examples were tested, and the purity of the recovered aluminum foil and copper foil was verified. The test results are shown in Table 1: Table 1 Performance Test Results

[0052] Based on Tables 1 and 2, and in conjunction with Example 1 and Comparative Example 1, it can be seen that the recovery rates of positive and negative electrode black powder and metal foil in Comparative Example 1 decreased, and the purity of the metal foil was significantly reduced. The reason for this may be that in Comparative Example 1, a wet crushing and separation method was used to separate the positive and negative electrode black powder and metal foil. During the crushing process, some particles were too small to be separated, resulting in difficulty in separating the metal foil particles and the positive and negative electrode powder, thus reducing the material recovery rate. Moreover, the residual binder also had a significant impact on the purity of the recovered material.

[0053] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.

Claims

1. A process for the complete recycling of waste lithium-ion batteries, characterized in that, The process includes the following steps: S1. Waste lithium-ion batteries are pretreated to obtain regular sheet-like materials; S2. The sheet-like regular material is microwave-baked in a vacuum environment, and the electrolyte is condensed and recovered along with the solid material. S3. The recovered solid material is evenly spread into layers, and the negative electrode is separated by eddy current separation; then the positive electrode and the separator are separated by spectral color sorting. S4. The positive and negative electrode sheets are irradiated under infrared light, and then separated by sieve to recover aluminum foil and copper foil respectively.

2. The waste lithium-ion battery recycling process according to claim 1, characterized in that, The S4 step specifically includes: S401. Irradiate the positive electrode sheet in the mid-infrared band for 10-30 seconds, and then sieve it through a drum screen to separate the positive electrode black powder and aluminum foil; S402. Irradiate the negative electrode sheet in the short infrared band for 20-40 seconds, and then sieve it through a drum screen to separate the negative electrode black powder and copper foil.

3. The waste lithium-ion battery recycling process according to claim 2, characterized in that, The mid-infrared band includes 5.5–6.5 μm; the short-infrared band includes 2.5–3.5 μm.

4. The waste lithium-ion battery recycling process according to claim 2, characterized in that, The power density of the irradiation in step S401 is 8–12 kW / m². 2 The power density of the irradiation in step S402 is 5–8 kW / m³. 2 .

5. The waste lithium-ion battery recycling process according to claim 1, characterized in that, The preprocessing in step S1 specifically includes: S101. Immerse the waste lithium-ion batteries in the pretreatment solution and discharge them until the voltage of the waste lithium-ion batteries is <0.05V. S102. Under an inert gas atmosphere, the discharged waste lithium-ion batteries are disassembled and crushed to obtain regular sheet-like materials.

6. The waste lithium-ion battery recycling process according to claim 5, characterized in that, The pretreatment solution comprises the following raw materials in the following mass fractions: 4.5-5.5% sodium chloride, 0.05-0.2% alkyl sulfate, and the balance water; the alkyl sulfate comprises one or more of sodium dodecyl sulfate, ammonium dodecyl sulfate, sodium dodecyl ether sulfate, sodium octyl sulfate, and sodium hexadecyl sulfate.

7. The waste lithium-ion battery recycling process according to claim 5, characterized in that, The solid-liquid ratio of the waste lithium-ion battery and the pretreatment solution is 1g:(4-6)mL.

8. The waste lithium-ion battery recycling process according to claim 1, characterized in that, The diameter of the flaky, regular material is 1 to 4 cm.

9. The waste lithium-ion battery recycling process according to claim 1, characterized in that, The microwave baking temperature is 90–110°C, and the baking time is 10–30 minutes.

10. The waste lithium-ion battery recycling process according to claim 1, characterized in that, The waste lithium-ion batteries include ternary lithium batteries and lithium iron phosphate batteries.

Citation Information

Patent Citations

  • Waste battery crushing and sorting line

    CN117655066A

Cited By

  • Composite efficient external discharge method for waste batteries

    CN121769310A